KUALITAS SPERMA EJAKULAT PEJANTAN AYAM KUKUAK BALENGGEK PADA PENGANDANGAN TUNGGAL TERISOLASI (Ejaculated Sperm Quality of Isolated Single Caging of Balenggek Chickens) - Ramadhan Sumarmin; Elsa Yuniarti; Abdul Razak (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
The Balenggek chicken is a long crower type fowl. This fowl have isolated and caging in single cage for years to result the long crower sound.This study was carried out to identify the influence of fed to the ejaculate sperm quality of balenggek chickens. First, the sperm were collected from isolated caging of Balenggek fowl more or less than three years and un-isolated caging of Balenggek fowl as control group. Second, the sperm were collected from isolated caging of Balenggek fowl more or less than three years and un-isolated caging of Balenggek fowl as control group, after treated by 124 ComFed for three months. The sperm were collected by massages methods and analyze with counting chamber of Improve Neubauer. Slides of sperm were stained by Eosin. Variables observed were sperm ejaculated, colours, and sperm consistency. The results shows that the sperm quality of Balenggek fowl increased (from 2.5 billion sperm/ml to 3.5 billion sperm/ml) significantly higher (p<0.05) in isolated caging fowl with reschedule feeding. Sperm color and its consistency were increased from + (c quality) to ++ (b quality). It can conclude that single caging could decreased the ejaculated sperm of Balengggek chickens quality and it. could reveal increased after it treated by 124 ConFed.